MSME Product Marketing Strategy Through the Implementation of Digital Marketing in Ancolmekar Village - Firmansyah, Arif; Lestari, Shifa; Hayatun, Hayatun; Puspitasari, Intan; Ramdaniah, Delia Nur; Putri, Viana Lifianty; Hastian, Putri Welis; Sutarya, Ikhsan Ali; Kholik, Wildan Abdul; Muhaedi, Muhammad Mufid; Hasan, Muhammad Yuda (CV. Rayyan Dwi Bharata, 2025)
This research aims to assess the influence of digital marketing on UMKM product sales and is analyzed by comparing UMKM that use digital marketing as a means of promotion and sales with UMKM that do not use this strategy. don't use it. Apart from that, this research also examines the implementation of digital marketing strategies in Ancolmekar Village. This research uses a qualitative descriptive method, with data collected through interviews, observation and documentation. Research findings reveal that digital marketing has a positive impact on sales and profits of UMKM. Various digital strategy methods that are successful in promoting products